Case Report: Pemphigoid Nodularis—Five Patients With Many Years of Follow-Up and Review of the Literature - Szymanski, Konrad; Adaszewska, Alicja; Jakubowska, Beata; Kowalewski, Cezary; Pietrzyk, Ewelina; Wozniak, Katarzyna (Frontiers in Immunology, 2022)
Pemphigoid nodularis is a rare form of pemphigoid that joins the clinical picture of prurigo nodularis and the immunological features of bullous pemphigoid, which is therapeutically challenging. Here, we analyze five female patients with a long-lasting course of nodular pemphigoid in terms of clinical and immunological characteristics and therapy. All the patients fulfilled clinical and immunological criteria of nodular pemphigoid. We applied numerous techniques allowing the proper diagnosis: direct and indirect immunofluorescence, salt split skin, ELISA, BIOCHIP, and fluorescence overlay antigen mapping using laser scanning confocal microscopy. Our study showed that 4 of 5 patients fulfilled the clinical and immunological criteria of nodular bullous pemphigoid. Two out of 4 patients presented exclusively nodular lesions; in the other two patients, blisters and erythematous lesions preceded prurigo-like lesions by a few years. The remaining patient had clinical and immunological criteria of nodular mucous membrane pemphigoid, presenting oral erosions, scarring conjunctivitis, and numerous disseminated nodules on the skin. All the patients were treated with multiple medicines; however, it was observed that the use of clobetasol propionate on the entire body plus antidepressants best controlled the disease. Pemphigoid nodularis mainly occurs in elderly women. In cases with coexisting psychological problems, antidepressants should be considered as an important complementary therapy to the basic one with clobetasol propionate.